1990
DOI: 10.1029/jb095ib10p15751
|View full text |Cite
|
Sign up to set email alerts
|

Phase relations in the transition zone

Abstract: Phase relations in the systems MgO‐Al2O3‐SiO2 and CaO‐MgO‐SiO2 have been investigated experimentally at 166–226 kbar pressures and 1350°–2500°C temperatures with a split sphere anvil apparatus (USSA 2000). MgSiO3 ilmenite is stable to lower pressures (175 kbar) than found previously. CaSiO3 perovskite forms at P(bar)=15T(°C)+151,000. Three new high‐pressure phases are reported: a phase with the diopsidic composition (the CM phase), a high‐pressure polymorph of Al2O3, and superphase B with the tentative composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(128 citation statements)
references
References 51 publications
6
122
0
Order By: Relevance
“…The maximum shock pressure and temperature, as constrained by the former perovskite, are 25-40 GPa and c2,000 1C, respectively [14][15][16][17] . Other occurrences of high-P minerals indicate shock pressures of 13-25 GPa and temperatures of 1,700-2,600 1C in melt pockets [17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…The maximum shock pressure and temperature, as constrained by the former perovskite, are 25-40 GPa and c2,000 1C, respectively [14][15][16][17] . Other occurrences of high-P minerals indicate shock pressures of 13-25 GPa and temperatures of 1,700-2,600 1C in melt pockets [17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…15). Gasparik (1990) suggested that an as yet unanalyzed hydrous magnesium silicate synthesized at 18.6 GPa and 1873 K possesses this structure and further studies on that material are in progress.…”
Section: Tv~]si Silicate Isomorphs Of Transition-metal Oxidesmentioning
confidence: 99%
“…MgSiO3 ilmenite is a high pressure polymorph of enstatite that is stable to temperatures as high as 2100 K in the Mg-metasilicate system [Gasparik, 1990]. In the mantle, the stability field of this phase is restricted to lower temperatures by the presence of A1 which tends to stabilize garnet at the expense of ilmenite.…”
Section: Introductionmentioning
confidence: 99%